Getting started with Oracle SOA Suite 11g R1 : a hands-on tutorial : fast track your SOA adoption : build a service-oriented composite application in just hours! /: a hands-on tutorial : fast track your SOA adoption : build a service-oriented composite application in just hours!. (©2009) - Unknown
No abstract available